Pengaruh Pertumbuhan Penjualan Dan Likuiditas Terhadap Profitabilitas (Pada Perusahaan Consumer Goods yang Terdaftar Pada BEI Tahun 2006-2011) - Supriyatna, Rio Kartika; Rahim, Anwar; Indupurnahayu, Indupurnahayu (Jurnal Manajemen, 2018)
This research aims to analyze whether or not the variables of sales growth and liquidity have influence to the profitability rate of consumer goods companies in sub sector of foods and baverage department in Indonesia. This research used multiple regression analysis method to find out the effect of independent variables, which are sales growth and liquidity to the profitability rate (ROA) of the company. Data proces using software Eviews 6 The result of this research shows that sales growth variable can influence a positive significant to profitability amounted 4,233436% of consumer goods company, while liquidity variable can affect a negative significant to profitability amounted 0,214522% influence to profitability of consumer goods company especially in sub sector of foods and baverages that enlist in BEI at the year 2006-2011. The research sales growth and liquidity simoultaneously have an influence to profitability of consumer goods are amounted 67,9247%, the rest is 32,0753 influence by another variable that do not conduct in model in this reseach.